The Korean mind understanding contemporary Korean culture - De Mente, Boye. (Tuttle Publishing, 2012)
"Koreans have a unique character and personality that sets them apart from all other Asians. And although Korean attitudes and behavior may be influenced by the modern world, the Korean mindset is still very much shaped by ancient culture and traditions. In The Korean Mind, Boye Lafayette De Mente explores the meanings and cultural context of the most important "code words" of the Korean language, terms whose significance goes well beyond their literal definitions. The reader is given insights into the character and personality of the Korean people, providing bridges for communicating and interacting with them."--Publisher's description.